AFTER ALL, WHO WENT TO VOTE IN 2022 - Nicolau, Jairo (2024)
The 2022 presidential election was the most competitive ever held in the country. In a contest with such uncertain outcomes, details that were often overlooked in past elections could make a difference in the result. Among these, voter abstention gained special attention in both rounds. The belief that voter turnout could influence the election outcome guided the campaign coordinators of Lula and Bolsonaro to act in favor of voter turnout during the final stretch of the campaign. This study analyzes the turnout rates and sociodemographic profile of the voters who went to the polls and those who abstained from voting in both rounds in 2022. We will also examine the profile of those who justified their vote. The results indicate that the voter turnout rate in the 2022 elections (79% in the first round, 80% in the second round) is similar to previous elections. The novelty is that the percentage of voters who turned out in the second round was, for the first time, higher than that of the first round.